Performance of Geopolymer Concrete Deep Beams with Variation in Shear Reinforcement Ratio - Rifkah, Rifkah; Saloma, Saloma; Nurjannah, Siti Aisyah; Saggaff, Anis (Journal of Engineering and Technological Sciences, 2026)
The construction industry's demand for sustainable alternatives to Portland cement has prompted investigation into geopolymer concrete (GC) as a replacement for normal concrete (NC) in deep beam applications, where structural behavior with varying shear reinforcement ratios remains insufficiently understood. This study examines the structural performance of GC and NC deep beams under monotonic loading through experimental testing and numerical modeling of six specimens—three NC (NC1, NC2, NC3) and three GC (G1, G2, G3)—with shear reinforcement ratios of 0.157%, 0.314%, and 0.628%, using LVDT sensors for displacement measurement and finite element analysis for stress–displacement validation. Results show that GC beams achieved higher maximum loads (700–1038 kN) than NC beams (500–742 kN), supported by superior compressive strength (68.36 MPa vs 43.6 MPa), greater energy dissipation (2897.54–7212.62 kN·mm vs 1340.96–2513.86 kN·mm), and improved shear capacity (ratio 0.74 vs 0.66). Ductility ratios ranged from 3.07–4.65 for NC and 1.62–2.10 for GC specimens. The enhanced performance of GC is attributed to its higher material strength, both materials exhibited similar stress distributions aligned with the strut-and-tie model and compression-controlled failure via diagonal strut formation between the loading points and supports. This study concludes GC offers strong potential as sustainable deep-beam material, achieving 40–48% higher maximum loads while maintaining comparable deflection behavior, with optimal performance at a shear reinforcement ratio of 0.628%. Experimental numerical differences remained below 1.5%. Future work should address long-term durability under cyclic loading and optimization of bond performance between GC and reinforcement materials.